Associations, réseaux et ambitions nationales des comparatistes de la fin du xixe siècle à la Seconde Guerre mondiale - Jean-Louis Halpérin (Clio@Themis, 2017)
With a point of departure in the 1900 Paris Congress and its image, this paper tries to study the relationships between the international dimension of the intellectual webs created by specialists in comparative law and the national origins of these jurists, that were likely to be the source of nationalist bias. The first part focuses on the national societies founded at the end of the nineteenth century: the Société de Législation Comparée, the Internationale Vereinigung für vergleichende Rechtswissenschaft und Volkswirtschaftslehre, the Society of Comparative Legislation. The second part concerns the multinational institutes of comparative law that were established after World War I : the International Academy of Comparative Law and Unidroit.